The Cenozoic Abanico Rift System: Implications of Increased Southward Extension in the Southern Central Andes, in Chile - Jara-Munoz, P (Elsevier Ltd, 2024)
The late Eocene-Early Miocene intra-arc Abanico extensional basin represents a major feature in central Chile (∼31°-42°S). Such basin system concentrated the magmatic activity along this Andean region and hosted locally more than 3.000 m of volcanic and volcaniclastic deposits (Abanico Formation) over a southward thinning crust (<35 km thick). South of 34°30′S, major changes occur in and out of the basin realm that modify the rather regular distribution of the geological features observed northwards, namely: 1. Southward termination of the exposures of the Farellones Formation, 2. Increased presence of pre-Abanico volcanic and plutonic exposures in the basin realm, 3. Southward width increase of the basin, 4. Abrupt end in the Maule region of the Cretaceous plutonic swaths exposed in the eastern Coastal Cordillera and westward bend of the swaths of Mesozoic units, 5. Increased presence of primitive volcanic rocks in the west-side of the basin, and 6. Presence, south of 36°S, of the Cura-Mallín Formation on the east-side of the basin. These changes are caused by the oblique orientation of the Abanico basin relative to the Mesozoic structural and paleogeographic trends and are enhanced by the increased southward opening of the basin. This opening would have occurred through a westward scissors-like rotation of the block of continental crust located west of the basin, which corresponds to the present-day Coastal Cordillera south of 34°30′S. The eastern border, which is represented by the El Diablo fault, remained essentially fixed. The westward rotation is supported by the north-northeast orientation of the Mesozoic plutonic and stratified swaths south of 34°30′S. Additionally, the swaths of Mesozoic rocks are obliquely interrupted by the similarly oriented western border of the basin. Previous analogue models designed to understand the opening and closure mechanisms of an extensional basin show that greater extension and subsidence in the basin occur next to the mobile border, which in the Abanico basin was located on its west side. This observation aligns with the increased southward presence of primitive volcanic rocks, like the Colbún Formation, in the region where crustal thinning would have been greater. Analogue models show that the increased southward extension allowed the development of wider depocenters. In the Maule region, an eastern depocenter near the El Diablo fault, hosted the Early to Middle Miocene deposits of the Cura-Mallín Formation. During contraction, deeply rooted reverse faults can involve basement rocks of the basin and bring them up to the surface as observed in the Abanico basin realm in the Tinguiririca and Maule regions. This study also highlights the continuity and importance of the El Diablo fault in the configuration of the basin. It is shown that, notwithstanding the existence of major changes south of 34°30′S, this fault represents a major structural element that remained unchanged along the Andean segment comprised between ∼32° and 36°30′S separating the Cenozoic deposits to the west from Mesozoic deposits to the east. This fault can be traced continuously from, at least, the Aconcagua valley (33°S) to the Maule region (36°30′S), and most probably extends further south. Apart from separating the Cenozoic Abanico basin deposits from the Mesozoic units involved in the east-vergent Andean fold-thrust belt, its trace forms an almost straight line that connects the Palomo, Tinguiririca, Planchón-Peteroa, Descabezados, San Pedro and Rezago volcanic centers and complexes, hot-springs, and hydrothermal alterations. © 2024 Elsevier Ltd